The Effectiveness of Lemon Aromatherapy on Emesis Gravidarum Among First-Trimester Pregnant Women at Sleman Primary Health Center, Yogyakarta - Syifaa Aliyyah Putri Rianto; Ellyda Rizki Wijhati (Jurnal Ners, 2026)
Emesis gravidarum is a condition of nausea and vomiting commonly experienced by women in the first trimester of pregnancy. Globally, 70–85% of pregnant women experience nausea and vomiting during the first trimester, while in Indonesia more than 60% of first-trimester pregnant women experience symptoms of varying severity. If inadequately managed, these symptoms may cause discomfort, reduced appetite, dehydration, and weight loss. This study aimed to analyze the effect of lemon aromatherapy on emesis gravidarum among first-trimester pregnant women at Sleman Primary Health Center, Yogyakarta. A quasi-experimental pretest–posttest control-group design was used. Purposive sampling recruited 32 respondents: 16 in the intervention group, who received lemon aromatherapy, and 16 in the control group, who received vitamin B6 according to primary health-care standards. Data were collected using observation sheets, checklists, and the Pregnancy-Unique Quantification of Emesis and Nausea (PUQE) score questionnaire. Data were analyzed using the Mann–Whitney non-parametric test. The results showed an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05), indicating a significant difference in emesis gravidarum between the groups after the intervention. After the intervention, all respondents (100%) in the lemon aromatherapy group were classified as having mild emesis, whereas in the control group only 1 respondent (6.3%) was classified as mild and 15 respondents (93.8%) remained in the moderate category. The reduction in nausea and vomiting may improve maternal comfort during daily activities and support adequate nutritional intake during pregnancy. Lemon aromatherapy may therefore be considered a complementary non-pharmacological intervention in antenatal care to help reduce emesis gravidarum in first-trimester pregnant women.